2009
DOI: 10.1253/circj.cj-08-0582
|View full text |Cite
|
Sign up to set email alerts
|

Altered Flow-Mediated Vasodilatation, Low Paraoxonase-1 Activity, and Abnormal High-Density Lipoprotein Subclass Distribution in Takayasu's Arteritis

Abstract: Background: Takayasu's arteritis (TA) is an idiopathic chronic inflammatory disease that causes occlusion of large arteries, but little is known about whether affected patients are characterized by endothelial dysfunction, different high-density lipoproteins (HDL) subclasses and paraoxonase-1 (PON1) activity. Methods and Results:In the present study, 30 patients with TA, 30 age-and gender-matched volunteers (controls) and 15 patients with essential hypertension were studied. Flow-mediated vasodilation (FMD) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 43 publications
1
11
1
3
Order By: Relevance
“…In combination with endothelial dysfunction, these abnormalities are likely to be important in the accelerated atherosclerosis in TA. 18,19 In the present study the severity of luminal narrowing in carotid arteries was positively correlated with degree of dyssynchronous expansion. These findings could support the relationship between abnormal arterial mechanical property and luminal narrowing in patients with TA.…”
Section: Vascular Alteration In Takayasu's Arteritissupporting
confidence: 58%
“…In combination with endothelial dysfunction, these abnormalities are likely to be important in the accelerated atherosclerosis in TA. 18,19 In the present study the severity of luminal narrowing in carotid arteries was positively correlated with degree of dyssynchronous expansion. These findings could support the relationship between abnormal arterial mechanical property and luminal narrowing in patients with TA.…”
Section: Vascular Alteration In Takayasu's Arteritissupporting
confidence: 58%
“…Although most studies showed decreased FMD in systemic vasculitis patients, one study showed that there was an enhanced FMD in patients with systemic vasculitis (19) where they had postulated that continued endothelial activation, even when the disease was clinically quiescent, could have led to this response. Unlike the results reported by Espinola-Zavaleta et al, (20) endothelial function as measured by FMD was found to be similar between patients with TA and normal controls (p>0.05). Hoffmann et al (21) showed that the efficacy of infliximab in TA patients acts by inhibiting the action of TNF-β, thereby decreasing iNOS activity.…”
Section: Discussioncontrasting
confidence: 99%
“…3,28,29 Moreover, TA patients had more endothelial dysfunction, lower paroxonase-1 activity, a higher proportion of large HDL2b and lower levels of HDL3b than in hypertensive patients and controls. 30 In clinical practice, the search for risk factors for CVD should not be overlooked in TA patients. Even though corticosteroid and immunosuppressive therapy was not associated with a protection against ischemic events in the present study, we believe that the proper treatment of TA disease activity is also important for preventing ischemic events altogether with aspirin use and the management of risk factors for CVD.…”
Section: De Souza Aws Et Almentioning
confidence: 99%